2013
DOI: 10.9789/2175-5361.2013v5n3p142
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Strategies of Adverse Events With Potentially Dangerous Medications

Abstract: Objective: To describe the strategies adopted by nurses for safe administration of a potentially dangerous drug in the intensive care unit. Method: This is an exploratory study literature which included articles about potentially dangerous drugs and medication errors in intensive care units published in the period 1998 to 2009. Results: The study included 16 items that resulted in three categories of potentially dangerous medications (amines, heparin and insulin), which were described the light of error preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Based on these considerations, we have drawn as the study object the establishment of some strategies for a safe administration of a potentially dangerous medication in intensive care unit environment and with the aim at describing the strategies adopted by the nursing professional for a safe administration of a potentially dangerous medication in intensive care unit scope. The results emerged from selection of 16 papers, relevant to the issue and the study object, which were analyzed and, subsequently, grouped into three medication categories: amines 7,11,14 , anticoagulants 17,20,22,23 and insulins 24,25,26,27,28,29,30 , being that such a grouping guided the study discussion. The aforementioned categories were created from the reading of papers.…”
Section: Accordingmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on these considerations, we have drawn as the study object the establishment of some strategies for a safe administration of a potentially dangerous medication in intensive care unit environment and with the aim at describing the strategies adopted by the nursing professional for a safe administration of a potentially dangerous medication in intensive care unit scope. The results emerged from selection of 16 papers, relevant to the issue and the study object, which were analyzed and, subsequently, grouped into three medication categories: amines 7,11,14 , anticoagulants 17,20,22,23 and insulins 24,25,26,27,28,29,30 , being that such a grouping guided the study discussion. The aforementioned categories were created from the reading of papers.…”
Section: Accordingmentioning
confidence: 99%
“…and Norepinephrine (pH=4.5). 14,15 With regard once more to the vasoactive medications administration, it was observed that there is a convention in clinical practice regarding the use of deep venous catheters, where we should give preference to always insert these medicinal drugs through the proximal route (which should be identified to provide exclusivity) since this has a "prime" (gauge), gravitational flow and infusion rate (ml/hr) lower than the other lumen (distal and medial), with a view to avoiding "flushes" of these medications and, consequently, their overdosage.…”
Section: Category I: Vasoactive Medications (Amines) 71114mentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown that glycemic digital collection may be inaccurate in critically ill patients due to the injury of peripheral perfusion, caused by the use of vasoactive drugs, the presence of edema and microcirculation disorders, as well as the collection of blood through venous access contaminated by intravenous solutions rich in glucose. 24 It is recommended that during the IV insulin infusion, the nurse should measure blood glucose every hour; this interval be increased every 2 or 3 hours in individuals with glucose control within the target in the last 6 to 12 hours, respectively.…”
Section: Use Of Subcutaneous (Sc) and Intravenous (Iv) Insulin In Thementioning
confidence: 99%